In-Situ Synthesis and Property Evaluation of High-Density Polyethylene Reinforced Groundnut Shell Particulate Composite (International Journal of Engineering Materials and Manufacture, 2021)
In-situ synthesis of high-density polyethylene (HDPE) reinforced groundnut shell particulate (GSP) composite with treated GSP within the range of 10-30 wt% at 10 wt% has been achieved. The adopted technique used in the production of the composite is melt mixing and compounding using two roll mills with a compression moulding machine. Properties such as hardness, tensile strength, impact energy and water absorption analysis were examined. The result revealed that addition of GSP increases the hardness value from 22.3 to 87 Hv. However, the tensile strength progressively decreased as the GSP increases in the HDPE. This trend arises due to the interaction between neighbouring reinforced particulate which appears to influence the matrix flow, thereby inducing embrittlement of the polymer matrix. It was also observed that water absorption rate steadily increased with an increase in the exposure time and the absorbed amount of water increases by increasing the wt% of the GSP. Analysing the obtained results, it was concluded that there were improvements in the hardness, tensile strength, impact energy and water absorption properties of the HDPE-GSP polymer composite when compared to unreinforced HDPE. On these premises, GSP was found as a promising reinforcement which can positively influence the HDPE properties of modern composites.